2018
DOI: 10.3390/su10124366
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of the New Rural Pension Scheme on Retirement Sustainability in China: Evidence of Regional Differences in Formal and Informal Labor Supply

Abstract: This paper evaluates the effect of China’s New Rural Pension Scheme (NRPS) on the retirement sustainability in forms of formal labor supply and informal labor supply in terms of care of grandchildren, using data from China Health and Retirement Longitudinal Study (CHARLS). We explore the regional differences of the NRPS effect on labor supply between the West and the other regions of China. Our analysis shows that rural Western China has a more severe problem of “ceaseless toil” compared to the rest of the cou… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 29 publications
(32 reference statements)
0
18
0
Order By: Relevance
“…QOL is quite low among single older people, and those who live with their spouses have a higher level of QOL [27]. While globally around one seventh of the older population lives alone [8], because the young population migrates to the cities, and older people are left alone [37], in the present study, 25% of the older people reported living alone. All of these studies corroborate what was found in this research, where approximately 69% of the older people claimed to live with their families, 54% of whom were married, and the QOL (73.35 ± 12.6) was remarkably high.…”
Section: Qol and Family Lifementioning
confidence: 48%
“…QOL is quite low among single older people, and those who live with their spouses have a higher level of QOL [27]. While globally around one seventh of the older population lives alone [8], because the young population migrates to the cities, and older people are left alone [37], in the present study, 25% of the older people reported living alone. All of these studies corroborate what was found in this research, where approximately 69% of the older people claimed to live with their families, 54% of whom were married, and the QOL (73.35 ± 12.6) was remarkably high.…”
Section: Qol and Family Lifementioning
confidence: 48%
“…Overall, our results imply that incentive pension is an effective mechanism in encouraging rural residents to participate in the pension programs, but current level of matching subsidies is not sufficient enough to improve participation or increase contributions. China's rural pension payments in general are less than 10% of per capital rural income, which is significantly lower than the social pension in other countries [6]. Our study shows the need to increase the fiscal subsides in China's rural pension system, and can provide useful implications in designing an effective pension system for rural residents.…”
Section: Discussion and Concluding Remarksmentioning
confidence: 77%
“…Historically, the Chinese rural elderly have relied heavily on their adult children as their main source of financial support. This traditional informal system of old-age provision has been weakening with the increased rural-to-urban migration flows as well as the higher life expectancy and lower fertility rate since the economic reforms in the 1980s [5][6][7]. China needs a sustainable pension system with a broad coverage and adequate benefits to provide a social safety net addressing the needs of the rural aging population.…”
Section: Introductionmentioning
confidence: 99%
“…The financial sustainability of the pension plan is a core theme of social welfare, especially in the era of population aging. Due to its close relations with macroeconomic development indicators, such as the gross domestic product, government revenue, local labor supply, and employment, as well as individual decisions on bearing children, consumption, saving, and retirement at the micro level [4,[15][16][17][18], policy reforms have been taken to enhance the sustainable capacity of the pension plan.…”
Section: Literature Reviewmentioning
confidence: 99%